Merawat Ciptaan Allah: Implementasi Eko Eklesiologi Dalam Tindakan Nyata Membersihkan Jembatan Lapogambiri - Simangunsong Cindy Balos; Marina Dilon Sipahutar; Kronika Pasaribu; Daud Sagala; Charli Manik; Liyus Waruwu (Indo Publishing, 2025)
The environmental crisis demands an active role for the church, and this theological context is known as Eco-Ecclesiology, which is a theological understanding of the church in its relationship with the environment. This study aims to describe the implementation of Eco-Ecclesiology in the concrete action of cleaning the Lapogambiri Bridge, analyze the factors that influence it, and evaluate its impact on public awareness in Tarutung, North Tapanuli. The Lapogambiri Bridge was chosen as the focus because its condition is experiencing problems with garbage accumulation, which pollutes the river and causes an unpleasant odor. This study uses a descriptive qualitative approach with field research. Data collection techniques include direct observation, structured and semi-structured interviews, documentation, and literature study. Primary data sources were obtained from interviews with community leaders, village officials, and village heads, as well as field observations. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the activity of cleaning the Lapogambiri Bridge is a concrete manifestation of the implementation of Eco-Ecclesiology, which is believed to be a real action that reflects the ecological spirituality of the church. This action is based on the Theology of Creation (stewardship mandate) which requires the church to be an agent of renewal and care for creation. This implementation includes practical dimensions such as planning and implementing the clean-up program, as well as a symbolic dimension (the bridge as a link between humans and nature and faith and action). This action not only improves the quality of the physical environment, but also successfully fosters ecological awareness and strengthens the culture of mutual cooperation in the community. In conclusion, the practice of cleaning the bridge proves that the church can play a role as an agent of ecological change that is able to build a culture of environmental care in a sustainable manner, where faith is practically manifested in efforts to maintain the cleanliness and sustainability of God's creation.